Prediksi Pengaruh Perencanaan Biaya, Pengendalian Biaya, Anggaran Biaya Covid-19 Pada Keuangan Pemerintah Daerah - Lesi Hertati; Inten Meutia; Rochmawati; Otniel Safkaur; Peny Cahya Azwardi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
The function of the regional government budget is needed as a guide to determine steps to achieve the goal of realizing a just and prosperous society based on the 1945 constitution. Then the control function is needed to see how the steps have been carried out so as not to deviate from planning. which has been budgeted. Good budget and control functions will be able to create efficiency, in operations that can carry out control of these costs. Regional financial accounting data aims as a control tool. Control is a directing power, so that the purpose of correcting deviations that has been determined is to achieve an efficient and effective goal. Accounting data can be used as a tool for making decisions for local governments appropriately and quickly. For the many types of budgets contained in the regional government of the Covid-19 era, the realization of the Covid-19 cost budget is intended for people to look down to support their economy in the midst of the shock of the Covid-9 outbreak, which is not yet clear when it will end. The budget plays an important role in local government in order to create a just and prosperous society. This research was conducted at the district / city government in South Sumatra. The results show that cost planning, cost control, covid-19 era budget costs affect local government finances to help the economy of the people affected by the Corona Virus. The test tool used is SEM Lisrel, then the method used is this research method is descriptive and verification methods.